Attachment and the Management of Empathic Accuracy in Relationship-Threatening Situations - Simpson, Jeffry A. (Pers Soc Psychol Bull, 2011)
We tested how attachment orientations are related to empathic accuracy (i.e., the accuracy with which one infers a partner’s private thoughts/feelings) during attachment-relevant discussions. In Study 1, married couples were videotaped while discussing a severe or a less severe relationship issue that involved intimacy or jealousy. In Study 2, dating couples were videotaped while trying to resolving a relationship conflict. Consistent with the revised Empathic Accuracy Model (Ickes & Simpson, 2001), highly avoidant individuals were less empathically accurate in general in both studies. Relative to less anxious persons, highly anxious individuals were more empathically accurate when discussing intimacy issues that posed a potential threat to their relationship (in Study 1), and when they were rated as more distressed when discussing a relationship conflict (in Study 2). The findings are discussed in terms of how highly anxious and highly avoidant people differentially “manage” empathic accuracy to regulate negative affect and facilitate their interpersonal goals.